Pengaruh Kombinasi Hormon Tumbuh Giberelin dan Auksin terhadap Perkecambahan Biji dan Pertumbuhan Tanaman Karet (Hevea brasiliensis Mull. Arg.) - Kunta Adi Tetuka; Sarjana Parman; Munifatul Izzati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Rubber tree (Hevea brasilliensis Mull. Arg.) are commodities that have an important role in Indonesia. Gibberellin and auxin can accelerate seed dormancy breaking. The aim of this research was to study the effects of gibberellin and auxin on the germination and growth of Hevea brasilliensis Mull. Arg. This research was conducted in December 2014 until Pebruary 2015 in Bringin village, sub district of Bringin, Semarang Regency and Laboratory structure and function of plant biology, FSM Diponegoro University. The arrangment used is the full factorial pattern of random design (RAL) with two factors, namely the gibberellin (G0,G1,G2) and auxin (I0,I1,I2). This research using nine treatments, each of treatment are three replicates. Parameters were observed such as percent of germination, rate of germination, height of plant, number of leaves,length of the roots, wet weight, and dry weight. The analysis of data used is Analysist of Variances (ANOVA), if it shows significant results then continued with the test duncan’s multiple test (DMRT)in fact 95% level. The results showed that the hormone gibberellin 100 ppm to provide maximum results for improving germination percentage and germination rate Hevea brasilliensis Mull. Arg. Gibberellin100 ppm increasing germination percentage up to 28% and germination rate up to 45%. Combination of 200 ppm gibberellin and auxin 100 ppm to provide maximum results for plant height with the increase reached 61%, wet weight up to 100 % and dry weight up to 159%. Key words: Hevea brasilliensis Mull. Arg., gibberellic acid, indol-3-acetic acid, germination, growth.